Exploring the Clinical and Genetic Spectrum of Steroid Resistant Nephrotic Syndrome: The PodoNet Registry - Trautmann, Agnes; Lipska-Ziętkiewicz, Beata S.; Schaefer, Franz (Frontiers in Pediatrics, 2018)
Background: Steroid resistant nephrotic syndrome (SRNS) is a rare condition, accounting for 10-15% of all children with idiopathic nephrotic syndrome. SRNS can be caused by genetic abnormalities or immune system dysfunction. The prognosis varies from permanent remission to progression to end-stage kidney disease (ESKD); post-transplant recurrence is common. Objectives: The PodoNet project aims to explore demographics and phenotypes of immune-mediated and genetic forms of childhood SRNS, to assess genotype-phenotype correlations, to evaluate clinical management and long-term outcomes, and to search for novel genetic entities and diagnostic and prognostic biomarkers in SRNS. Methods: In 2009, an international registry was established to collect retro- and prospective information on renal and extrarenal disease manifestations, histopathological and genetic findings, family history, pharmacotherapy responsiveness and outcomes. To date, more than 2000 patients have been enrolled at 72 pediatric nephrology centers, constituting the largest pediatric SRNS cohort assembled to date. Results: In the course of the project, traditional Sanger sequencing was replaced by NGS-based gene panel screening covering >30 podocyte-related genes complemented by whole exome sequencing. These approaches allowed establishing genetic diagnoses in 24% of the patients screened, widened the spectrum of genetic disease entities presenting with SRNS phenotype (COL4A3-5, CLCN5), and contributed to the discovery of new disease causing genes (MYOE1, PTPRO). 42% of patients responded to intensified immunosuppression with complete or partial proteinuria remission, 58% turned out multi-drug resistant. Medication responsiveness was highly predictive of favorable long-term outcome, whereas a genetic disease was associated with a high risk to develop ESKD during childhood. Genetic SRNS forms were generally resistant to immunosuppressive treatment, justifying avoiding such pharmacotherapies altogether once a genetic diagnosis is established. Even symptomatic antiproteinuric treatment with RAS antagonists seems to be challenging and of limited efficacy in genetic SRNS forms. The risk of post-transplant disease recurrence was around 30% in non-genetic SRNS whereas it is negligible in genetic cases. Conclusion: In summary, the PodoNet Registry has collected detailed clinical and genetic information in a large SRNS cohort and continues to generate fundamental insights regarding demographic and etiological disease aspects, genotype-phenotype associations, the efficacy of therapeutic strategies, and long-term patient and renal outcomes.